Fermentasi Nira Nipah Menjadi Bioetanol Menggunakan Teknik Immobilisasi Sel Saccharomyces Cerevisiae - Ella Awaltanova; Syaiful Bahri; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The high dependence of fuel resource such as oil, coal, and gas will influence depletion of fossil resources (oil, natural gas, and coal). Therefore, it is important to study conversion of biomass to bioethanol as renewable energy to overcome dependence on fossil fuels. Production of bioethanol using free cell in fermentation and it several disadvantages in separation of yeast cells and biethanol concentration. This research was conducted the fermentation of nypa sap with immobilization cell, using tween 80 and ergosterol as suplement to obtain high concentration of bioethanol as well as avoid osmosis in cells . This work is aimed to study of bioethanol production from nypa sap using immobilized cells, to determine effect of cell immobilization weight and fermentation time to bioethanol, and to obtain maximum conditions on the process. Fermentation was conducted in 2L fermentor having variations of fermentation time such as 24, 36, 48, 60, 72, 84, and 96 hours respectively and cell immobilization weight e.g. 5 %w/v, 10 %w/v, 15 %w/v, and 20 %w/v respectively, and also addition of tween 80 of 0,2% v/v and ergosterol of 0,5 g/l. The concentration of bioethanol was increased with increases of immobilized cells. Maximum conditions of bioethanol production from nypa sap using immobilized cells are shown having cell immobilization weight of 20% w/v and fermentation hours 96th about 17,574 % v/v equal with 138,708 mg/ml. Keywords : bioethanol, ergosterol, immobilized cells, nypa, sacharomyces cereviceae, tween 80